The entwinement of politics, arts, culture and commerce in staging social and political reality to enhance democratic communication - Mutibwa, Daniel H. (University of Southern California, Annenberg School of Communication and Journalism, 2016)
This article explores how four British and German theatre companies that originated in the countercultural era continue to survive in an increasingly austere economic climate. Although their survival strategies have been marked by remarkable resilience, this has sometimes affected the quality of engagement with their socio-political enquiries and interventions informed in part by radical approaches to theatre-making that make these companies so distinctive. The article draws on relevant theoretical perspectives and ethnographic fieldwork to argue that whereas some constitutive elements of radical theatre are discernible, these are increasingly being constrained by elitist/political and market forces that threaten to undermine these companies’ unique significance as conduits for democratic communication.